Bumelia Webworm Urodus parvula (Edwards 1881) (Insecta: Lepidoptera: Urodidae) - Donald W. Hall (EDIS, 2018)
Includes: Introduction - Nomenclature and Classification - Distribution - Description - Life Cycle - Hosts - Natural Enemies - Defenses - Selected References